Teacher Competence and Learning Environment as Predictors of Students’ Academic Achievement in Public Secondary Schools in Oro Metropolis - Adebayo, David Obafemi; Blessing, Ifeoluwa; Faysol, Faysol (Buletin Konseling Inovatif, 2025)
This study investigated the influence of teacher competence and the learning environment on students' academic achievement in public secondary schools in Oro Metropolis Area of Kwara State. The importance of teachers' qualifications, teaching methods, and the physical and psychological classroom environment has been widely recognized in educational research. However, the interplay between these factors and their combined effect on students' academic success in the local context of Oro remains underexplored. This study adopts a correlational research design to examine these variables in 10 selected secondary schools in the local government area. A sample of 200 students and 50 teachers will be randomly selected to participate. Data was collected through questionnaire forms and standardized tests to evaluate teacher competence, the quality of the learning environment, and students' academic achievement. Findings highlighted significant relationships between teacher competence, learning environment, and student achievement, providing insights into areas for improvement in local educational policies and practices.